THE ROLE OF CASE DEGREES AND RECONSTRUCTION IN STRENGTHENING INVESTIGATORS' CONFIDENCE IN CRIME EVIDENCE - Dida, Qaulan Sadida (Universitas Negeri Semarang, 2024)
The law enforcement process for suspected criminal acts begins with an investigation process by the police. An investigation is carried out with the aim of searching for and finding an incident that is suspected of being a criminal act so that the next stage, namely investigation, can be carried out. This research uses a normative juridical research type with a qualitative approach. Based on secondary data and primary data. The results of this research show that: (1) The role of case title and reconstruction in the Indonesian criminal justice system is as a guide in the criminal investigation process. (2) Case title and reconstruction play a role in assisting investigators in collecting evidence and strengthening investigators' confidence in collecting evidence to uncover a criminal act. The conclusion from this research is that the case title plays a role in helping investigators collect evidence, while the reconstruction acts as a guiding evidence that strengthens investigators' confidence in uncovering criminal acts.